?Evaluation of Pakistani Sweet Basil Oil for Commercial Exploitation (Biological Sciences - PJSIR, 1995)
tified by comparison with their standard samples in the GCand fragmentation pattern of the individual component inthe mass spectra [5-6]. The percentage composition was foundby gas chromatography on the basis of peak areas. The compoundsof lower content (less than 0.1%) were not identified